Connecting puzzles’ pieces to build an action plan for end user education - mancini, Cristina; Barbaro, Annarita; Zedda, Monica (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
In the last few years end user education has become increasingly important in the daily work of biomedical librarians: new technologies, databases, and innovative systems for accessing information have made information retrieval more complicated and challenging for librarians and users alike. The Library of the Istituto Superiore di Sanità (ISS) decided to plan a diversified program of seminars covering different library services to promote an effective use of technologies and library resources. Data were collected during 2018 utilizing a self-developed user satisfaction survey questionnaire formulated in order to identify the real satisfaction level of our users and in order to improve our activities.